Penerapan Metode Visual Schedule Dalam Meningkatkan Bina Diri Memakai Sepatu Pada Anak Autis Kelas I Di SLB Jenetallasa - Siti Nurkhaliza Bahar; St. Kasmawati; Tatiana Meidina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the issue of low proficiency in the self-care skill of putting on shoes among a first-grade female student with autism at SLB Jenetallasa. The research questions are: (1) What was the student's ability to put on shoes before the implementation of the visual schedule method? (2) What was the student's ability to put on shoes after the implementation of the visual schedule method? (3) Was there an improvement in the ability to put on shoes through the implementation of the visual schedule method? The study aims to assess the self-care skill of putting on shoes before and after the intervention and to determine the extent of improvement. A quantitative approach with a descriptive research design was employed. The research subject was a first-grade female student with autism (initials: G) at SLB Jenetallasa. Data collection was conducted using tests, and data analysis involved comparing pre-test and post-test results regarding the self-care skill of putting on shoes. The results indicate that the skill level prior to the intervention was in the "very low" category (0% pre-test score), whereas after the implementation of the visual schedule method, it rose to 92.3%, falling into the "very good" category. Thus, the visual schedule method is effective for improving the self-care skill of putting on shoes in a first-grade student with autism at SLB Jenetallasa.